HUBUNGAN DUKUNGAN SOSIAL ORANG TUA DENGAN SELF-EFFICACY SISWA SMKN 2 KOTA JAMBI - Eliza, Riana; Sutja, Akmal; Alridho Lubis, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the importance of implementing student self-efficacy in supporting the learning process and student development at school. One factor suspected to influence this is social support provided by parents. Therefore, this study aims to determine the relationship between parental social support and student self-efficacy at SMKN 2 Jambi City in the 2025/2026 academic year. This research used a quantitative approach with a correlational method. The population in this study were all 10th and 11th grade students majoring in Accounting and Institutional Finance (AKL), totaling 355 students. The sample size was 188 students determined using the Slovin formula. Data were collected using a Likert-scale questionnaire and analyzed using SPSS 26. The results showed that parental social support was in the high category at 69.7%, while student self-efficacy was also in the high category at 65.5%. Correlation analysis using Pearson Product Moment showed a correlation coefficient of 0.506 with a significance level of 0.000 (<0.05), indicating a positive and significant relationship between parental social support and student self-efficacy. This relationship is considered moderate, indicating that the higher the level of parental social support, the higher the student's self-efficacy, and vice versa. These findings indicate that parental social support plays a crucial role in shaping students' self-confidence in facing academic tasks and challenges. Therefore, collaboration between schools and parents is necessary to support students' psychological development, particularly in enhancing self-efficacy.